The Spanish mortgage crisis: Evidence of the concentration of foreclosures in the most deprived neighbourhoods - Gutiérrez, Aaron; Domènech, Antoni (DIE ERDE – Journal of the Geographical Society of Berlin, 2017)
The Spanish mortgage crisis has resulted in a massive process of home dispossession through foreclosures. This process forms part of the logics of accumulation by dispossession supported by the Spanish financial and real estate model. The article uses the city of Lleida as case study to show that the effects of this phenomenon has tended not to be spatially homogenous, but rather to be more concentrated in the most deprived urban areas. The analysis has been focused on two approaches: (1) identifying the characteristics of housing affected by foreclosure processes that have resulted in evictions, and; (2) defining the spatial distribution patterns of this housing. This work demonstrates how evictions due to mortgage foreclosures have followed very clear patterns. Firstly, they have predominantly been focused on lower quality housing (identified in this study as the cheapest and smallest properties). Secondly, Getis-Ord Gi* spatial statistic has been used to show that they have been concentrated in the most deprived areas of the city. Both issues confirm the central hypothesis of our study: the Spanish mortgage crisis has exacerbated existing urban disparities.